THE ROLE OF PEDAGOGICAL CONDITIONS IN DEVELOPING HEALTHY LIFESTYLE SKILLS (American Journal of Pedagogical and Educational Research, 2025)
The article reveals the decisive role of pedagogical conditions — hygienic, moral-ethical, and social factors — in the formation of healthy lifestyle (HLS) skills. The impact of stress, technological pressure, and hygiene requirements in the educational environment is scientifically analyzed. The necessity of an integrated, interdisciplinary approach to promoting HLS is substantiated, and practical solutions to current problems are proposed.